Shelf-invading low-oxygen waters control Cenozoic organic carbon burial rates - Rosalind E. M. Rickaby; Thomas J. Wood; Zunli Lu; Christian J. Bjerrum (Proceedings of the National Academy of Sciences, 2026)
The thermostatic mechanisms of Earth’s persistent habitability remain unresolved. High-resolution Cenozoic C isotope records, P accumulation, and coarse-fraction I/Ca allow recalculation and assessment of controls on the global proportion of total carbon buried as organic carbon ( f org ), a regulator of atmospheric CO 2 and O 2 . f org was suppressed during the Eocene hothouse, coincident with an oxygenated water column and low water-column phosphate. With decreased sea level, the area for efficient organic carbon and phosphate sedimentary burial diminished, leading increasingly to greater water-column phosphate, higher primary productivity, and emergent water column deoxygenation. The sea-level influence on the areal extent of high sedimentation in shelf regions acts as a control on phosphate availability for new production, respiratory demand, and ocean oxygenation, as proposed by hypsographic models [C. J. Bjerrum, J. Bendtsen, J. J. F. Legarth, Geochem. Geophys. Geosys. 7 , 1–24 (2006)]. During intermediate sea-level highs of the Neogene, pulses of enhanced organic carbon burial prevailed for multimillion years, in response to the redox recycling of phosphate when oxygen minimum zones with O 2 < 90 µmol/kg were present. We propose the existence of a self-limiting intermediate sea-level sweet spot with peak C org burial due to redox recycling of phosphate, whereby oxygen minimum zones (OMZ) with O 2 < 90 µmol/kg impinge on the most C org rich continental shelf sediments. Such a sweet spot has narrowed over Earth history due to deepening OMZs, stabilizing both atmospheric O 2 and CO 2 . Continental marine inundation controls on phosphate availability, and the sedimentary carbon flux, provide a positive-feedback and rectifier to perturbations during inception of the icehouse world.